2012
DOI: 10.1080/09571736.2011.585402
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the four walls: community-based learning and languages

Abstract: At a time when languages in universities are under pressure, Community Based Learning language courses can have many positive benefits: they can increase interest in language learning and they can foster greater engagement with learning, encouraging active learning, creativity, and teamwork. These courses which link the classroom and the community help address needs in the community; make languages more visible, and share resources. By giving students the opportunity to engage in practical work, their transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
4
11
0
5
Order By: Relevance
“…Apart from academic enhancement, the peer-tutoring service aided them in developing effective teacher dispositions, interpersonal communication skills and a strong sense of social responsibility. In terms of the personal growth gains, the present research confirmed the findings of prior studies, in which compassion, patience, tolerance and diligence were shortlisted as core values, and confidence, empathy, self-awareness and commitment as key competencies to develop as a result of service-learning (Ash & Clayton, 2004;Barnes & Caprino, 2016;Carver, 1997;Cone, 2012;D'Rozario et al, 2012;Eyler & Giles, 1999;Eyler et al, 1996;He & Prater, 2014;Hildebrandt, 2014;McFadden et al, 2002;Moely et al, 2002;Molee et al, 2010;O'Connor, 2012;Pak, 2013;Schelbe et al, 2014;Simons & Cleary, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Apart from academic enhancement, the peer-tutoring service aided them in developing effective teacher dispositions, interpersonal communication skills and a strong sense of social responsibility. In terms of the personal growth gains, the present research confirmed the findings of prior studies, in which compassion, patience, tolerance and diligence were shortlisted as core values, and confidence, empathy, self-awareness and commitment as key competencies to develop as a result of service-learning (Ash & Clayton, 2004;Barnes & Caprino, 2016;Carver, 1997;Cone, 2012;D'Rozario et al, 2012;Eyler & Giles, 1999;Eyler et al, 1996;He & Prater, 2014;Hildebrandt, 2014;McFadden et al, 2002;Moely et al, 2002;Molee et al, 2010;O'Connor, 2012;Pak, 2013;Schelbe et al, 2014;Simons & Cleary, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…As demonstrated by their greater reliance on foundational knowledge and application in their comments, the peer-tutoring service enhanced their understanding of the subject matter, enabled them to put it into practice in realistic situations, and stimulated critical thinking in peer groups. On the academic learning front, the current research corroborated the findings of many earlier studies, which emphasised the facilitating influence of academically-based community service on the real-life application of the specialised knowledge and job skills trainees have merely encountered in the comfort zone of their university classrooms (Ash & Clayton, 2004;Barnes & Caprino, 2016;Butcher et al, 2003;Carver, 1997;Chupp & Joseph, 2010;Cone, 2012;Dodd & Lilly, 2000;D'Rozario et al, 2012;Eyler & Giles, 1999;Eyler et al, 1996;He & Prater, 2014;Hildebrandt, 2014;Kistler & Crosby, 2014;Litke, 2002;Molee, Henry, Sessa & McKinney-Prupis, 2010;O'Connor, 2012;Pak, 2013;Petersen, 2007;Schelbe et al, 2014;Simons & Cleary, 2006).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations